1995
DOI: 10.1088/0967-3334/16/2/004
|View full text |Cite
|
Sign up to set email alerts
|

Errors in prolonged electrical impedance measurements due to electrode repositioning and postural changes

Abstract: Long-term electrical impedance measurements are affected by specific errors. Electrode failure, changes in its impedance due to aging, and postural changes are among the most important. We analyse errors due to electrode replacement and body postural changes. Electrode replacement errors can cause impedance changes up to 5% of basal value. This is one of the most important factors in data reproducibility. Body postural changes also contribute to impedance variations. We have proposed the use of a reference pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 14 publications
1
41
0
Order By: Relevance
“…In our two subjects we observed similar impedance changes as reported in Lozano et al 30 where electrode dislocations by up to 1 cm caused a DZ rel,disp of up to 4.4% on arms and legs. The main reason for the displacement error is probably the change of the geometrical boundary conditions for the current ®eld.…”
Section: Assessment Of Abdominal Fatness By Impedance H Scharfetter Esupporting
confidence: 91%
See 1 more Smart Citation
“…In our two subjects we observed similar impedance changes as reported in Lozano et al 30 where electrode dislocations by up to 1 cm caused a DZ rel,disp of up to 4.4% on arms and legs. The main reason for the displacement error is probably the change of the geometrical boundary conditions for the current ®eld.…”
Section: Assessment Of Abdominal Fatness By Impedance H Scharfetter Esupporting
confidence: 91%
“…Experiments were carried out in only two persons (one male, one female, 23 and 25 y, 68 and 83 kg, 172 and 192 cm, respectively) because similar data were published previously for whole-body and segmental arrangements. 30 So it was just checked whether the data range was comparable. In addition to the con®guration in Figure 1 electrodes were placed 2 cm right from the original positions in order to simulate a transversal displacement.…”
Section: Reproducibilitymentioning
confidence: 99%
“…First, EIT is very sensitive to issues associated with the patient interface (i.e. electrodes Soleimani et al (2006); Lozano et al (1995) and cables Hong et al (2007)). The electrode contact to the body tends to have relatively high contact impedance, Z c , which also varies with time due to body movement, moisture on the contact surface and electrode replacement.…”
Section: Introductionmentioning
confidence: 99%
“…These sensors are susceptible to changes in temperature, sweat, and movement with exercise and breathing. For example, it has been shown that electrodes on the body surface give false readings due to electronic interference [4], patient movement, or sweat and peripheral edema [6], especially in long term monitoring applications [5].…”
Section: Introductionmentioning
confidence: 99%